Politics, development, and upazila - Shawkat Ali, A. M. M. (Dhaka : National Institute of Local Govt., 1986)
Review of a locally-elected government at district and thana levels.
Bibliography: p. 237-240.
Includes index.
Keywords: Rural development -- Bangladesh; Local government -- Bangladesh